Invertebrates Experimental Models in Toxicity Screening - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This edited book, Invertebrates-Experimental Models in Toxicity Screening, is intended to provide an overview of the use of conventional and nonconventional invertebrate species as experimental models for the study of different toxicological aspects induced by environmental pollutants in both aquatic and terrestrial ecosystems. Furthermore, it is hoped that the information in the present book will be of value to those directly engaged in the handling and use of environmental pollutants and that this book will continue to meet the expectations and needs of all interested in the different aspects of toxicity screening.